Computational Insights into the Radical Scavenging Activity and Xanthine Oxidase Inhibition of the Five Anthocyanins Derived from Grape Skin - Xiao-Qin Lu; Jindong Li; Bin Wang; Shu Qin (MDPI AG, 2024)
Anthocyanins, typical polyphenol compounds in grape skin, have attracted increasing interest due to their health-promoting properties. In this body of work, five representative anthocyanins (Cy-3-O-glc, Dp-3-O-glc, Pn-3-O-glc, Mv-3-O-glc, and Pt-3-O-glc) were studied using the density functional theory (DFT) to elucidate structure-radical scavenging activity in the relationship and the reaction path underlying the radical-trapping process. Based on thermodynamic parameters involved in HAT, SET-PT, and SPLET mechanisms, along with the structural attributes, it was found that the C4' hydroxyl group mainly contributes to the radical scavenging activities of the investigated compounds. Pt-3-O-glc exhibits a good antioxidant capacity among the five compounds. The preferred radical scavenging mechanisms vary in different phases. For the Pt-3-O-glc compound, the calculations indicate the thermodynamically favoured product is benzodioxole, rather than o-quinone, displaying considerably reduced energy in double HAT mechanisms. Additionally, the thermodynamic and kinetic calculations indicate that the reaction of •OH into the 4'-OH site of Pt-3-O-glc has a lower energy barrier (7.6 kcal/mol), a higher rate constant (5.72 × 109 M−1 s−1), and exhibits potent •OH radical scavenging properties. Molecular docking results have shown the strong affinity of the studied anthocyanins with the pro-oxidant enzyme xanthine oxidase, displaying their significant role in inhibiting ROS formation.